Can South Africa have the national health insurance (NHI)?: an exploration of the OR Tambo municipality district - Willies, Medinah (My University, 2022)
The National Health Insurance (NHI) in South Africa is in its early stages of implementation. With the first phase of pilot project implementation underway there is a lot of cynicism surrounding the states capacity to implement a policy as large as the NHI. South Africans have lost faith in the government’s ability to provide basic services as well as address issues at ground level. Rather than accept failure the government tends to produce short-term solutions that ultimately end up burdening the people, namely the poor majority. The research investigates the feasibility of policy implementation in the delivery of healthcare in regard to the relationship between the national and local levels of governments. It then goes onto discussing how this relationship translates into a national policy being implemented at local level in a rural setting. It makes the argument that the NHI governance structures entrenched in the principles of good governance need to be adhered to in coordinated and collaborative manner between the national and local tiers of government in order for the NHI to envision a successful implementation. Finally, it argues that the NHI in rural areas needs adjustments as the health disparities experienced in rural areas are not only a result of financial incapacity but also the socio-economic, infrastructural and topographical nature of these settings.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2020